Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.onc.1202510
|View full text |Cite
|
Sign up to set email alerts
|

JTB: A novel membrane protein gene at 1q21 rearranged in a jumping translocation

Abstract: 1q21 is frequently involved in di erent types of translocation in many types of cancers. Jumping translocation (JT) is an unbalanced translocation that comprises ampli®ed chromosomal segments jumping to various telomeres. In this study, we identi®ed a novel gene human JTB (Jumping Translocation Breakpoint) at 1q21, which fused with the telomeric repeats of acceptor telomeres in a case of JT. hJTB (human JTB) encodes a trans-membrane protein that is highly conserved among divergent eukaryotic species. JT result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 19 publications
(14 reference statements)
0
38
0
Order By: Relevance
“…In two recent reports of JT, it has been shown that the telomeric sequences were maintained. 12,20 In our case, no telomeric hybridization was found on the recipients. It has been suggested that transformation of myelodysplastic syndrome is associated with excessive telomere shortening which in itself favors recombinations.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…In two recent reports of JT, it has been shown that the telomeric sequences were maintained. 12,20 In our case, no telomeric hybridization was found on the recipients. It has been suggested that transformation of myelodysplastic syndrome is associated with excessive telomere shortening which in itself favors recombinations.…”
Section: Figurementioning
confidence: 78%
“…The JT breakpoint is sometimes located in regions known to contain DNA repetitive sequences, such as centromeres or the pericentromeric heterochromatin region. Nevertheless, the breakpoint may be observed in other regions as illustrated by the recent report of Hatakeyama et al 20 which identified a novel human gene JTB at 1q21 encoding a transmembrane protein. Three other donor chromosomes have been reported: 7q in a case of lymphoid blast crisis of CML, 3q and 11q in other cases of AML.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with this, a large number Chromosome 1q21 copy change and prognosis in myeloma R Fonseca et al of candidate genes in the 1q21 region (e.g., BCL9, MCL1, CKS1B and MUC1) have been pathogenically implicated in MM and other malignancies. 9,[28][29][30][31][32][33][34][35][36][37] More recently, integrated analysis of high-resolution array comparative genomic hybridization and GEP identified a high priority minimal region of DNA copy number change on 1q21. This 10 Mb region contain several genes including the aforementioned CSK1B, BCL9 and MCL1.…”
Section: Discussionmentioning
confidence: 99%
“…JTB was first identified as an open reading frame from the sequence near a fusion point at 1q21 translocated to telomeric repeats of acceptor telomeres in a case of jumping translocation and postulated to encode a protein of 16.4 kDa (Hatakeyama et al, 1999). An analysis of the protein structure revealed distinctive stretches in the Nand C-terminal regions (Hatakeyama et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…JTB was first identified as an open reading frame from the sequence near a fusion point at 1q21 translocated to telomeric repeats of acceptor telomeres in a case of jumping translocation and postulated to encode a protein of 16.4 kDa (Hatakeyama et al, 1999). An analysis of the protein structure revealed distinctive stretches in the Nand C-terminal regions (Hatakeyama et al, 1999). The N-terminal stretch consisting of highly hydrophobic amino acids supposedly functions as a signal sequence for secretion of the polypeptide or for recruitment to membrane compartments, being processed and removed during the process.…”
Section: Introductionmentioning
confidence: 99%